2016
DOI: 10.1063/1.4960053
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopic evidence for (NO)3 formation on Cu(111)

Abstract: The formation of (NO)3 on Cu(111) was recently reported based on scanning tunneling microscopy observations [A. Shiotari et al., J. Chem. Phys. 141, 134705 (2014)]. We herein report studies into this system using electron energy loss spectroscopy and verify the above findings through vibrational analysis. For the surface covered with mixed isotopes of N(16)O and N(18)O, we observed four peaks corresponding to N-O stretching vibrations, which were ascribed to the four isotopic combinations of the trimer. Dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 26 publications
5
16
0
Order By: Relevance
“…The adsorption energies calculated by using vdW functionals increase in the sequence NO < (NO) 2 < (NO) 3 -I < (NO) 3 -II. The results using vdW functionals indicate that NO molecules tend to pair up to form dimers, and then trimers on Cu(111), consistent with the experimental observations. Furthermore, we investigated a formation of NO tetramer ((NO) 4 ) on Cu(111) p (3 × 3), where one more NO molecule was added at the fcc-hollow site near (NO) 3 -II. The (NO) 4 has a rhombus geometry (Figure ) and the calculated E ads and E b are smaller than those for dimer and trimer, indicating that the NO tetramer is less stable than both the NO dimer and trimer.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…The adsorption energies calculated by using vdW functionals increase in the sequence NO < (NO) 2 < (NO) 3 -I < (NO) 3 -II. The results using vdW functionals indicate that NO molecules tend to pair up to form dimers, and then trimers on Cu(111), consistent with the experimental observations. Furthermore, we investigated a formation of NO tetramer ((NO) 4 ) on Cu(111) p (3 × 3), where one more NO molecule was added at the fcc-hollow site near (NO) 3 -II. The (NO) 4 has a rhombus geometry (Figure ) and the calculated E ads and E b are smaller than those for dimer and trimer, indicating that the NO tetramer is less stable than both the NO dimer and trimer.…”
Section: Resultssupporting
confidence: 80%
“…The adsorption site of NO on Cu(111) was originally assigned to a 2-fold bridge site and later it was assigned to a 3-fold hollow site . Koshida et al revisited this system by EELS at 100 K and verified the formation of the NO trimer on Cu(111) that is observed by STM, and the mode at 190 meV is reassigned to the N–O stretching modes of NO trimer rather than the NO monomer at the fcc-hollow site . As will be discussed below, we found that the stretching modes are blue-shifted when NO absorbed in the trimer configuration, and those modes for the NO trimer agree well with the aforementioned experimental data.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations